Piecemaker computer aided music transcription - Barnachea, Angelle (1995)
A computer-aided music transcription software is developed to help non-professional musicians and professional musicians alike in producing the standard musical piece notation of a monophonic piano musical passage. As a preliminary step in the transcription process, this musical passage is first digitized and then passed through the application to produce the said musical piece. What makes this current application different and attractive is that it does not make use of any MIDI hardware which could prove to be expensive for the non-professional users. Instead a Sound Blaster would be needed only in the creation of the input digitized file but will not actually be needed to run the program. Thus the application is functionally complete by itself. The current software provides the basic pitch detection and note duration determination algorithms. Also, a graphical interface is presented to let the user see the transcription process. Various recommendations are presented in this paper to provide directions for the would be extenders. Such recommendations include improving the over-all software performance through increased pitch detection accuracy.